Sydney’s Food Landscapes Agriculture, Planning, Sustainability - Zeunert, Joshua; Daroy, Alys (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2025)
XXII, 476 p. 113 illus., 111 illus. in color.